Dissociative Disorders with Haemolacria: Series of Case Reports - Rahman, Md Shafiqur; Karim, Md Rezaul; Islam, Mohammed Misbahul; Karim, Md Redwanul (Journal of Bangladesh College of Physicians and Surgeons, 2017)
Bloody tears (Haemolacria) are a rare symptom that can be caused by local or systemic pathology. It is one of the most alarming symptom in ophthalmology. Besides those, idiopathic cases have been reported. A case of hyperthyroidism where haemolacria was secondary to the condition has also been reported. Haemolacria are also reported as secondary to epistaxis. Psychogenic causes are described including Munchausen Syndrome by proxy. Here we describe a series of four cases of haemolacria along with bleeding from other sites, found as associated features of dissociative disorders. In this series, patients with age ranging from 14-17 years, three of them are female and one male have been included. Examination excluded local ocular and nasal pathology, coagulopathy and hyperthyroidism. In course of their illness, two of these cases met the DSM 5 criteria for both dissociative disorders and conversion disorders, rest of them have been diagnosed as mixed dissociative disorders. After appropriate intervention, three patients recovered completely and in one patient symptoms (also bleeding) recurred on re-exposure to the previous stress factors. We report three cases of Dissociative disorders and one with both dissociative and conversion disorder where bloody tears were one of the feature. To the best of our knowledge this is the first official report of its kind in Bangladesh. J Bangladesh Coll Phys Surg 2017; 35(1): 36-42